The effects of phosphatidic acid supplementation on strength, body composition, muscular endurance, power, agility, and vertical jump in resistance trained men. Issue 1 (December 2016) - Escalante, Guillermo; Alencar, Michelle; Haddock, Bryan; Harvey, Phillip
Abstract Background Phosphatidic acid (PA) is a lipid messenger that has been shown to increase muscle protein synthesis via signaling stimulation of the mammalian target of rapamycin (mTOR). MaxxTOR® (MT) is a supplement that contains PA as the main active ingredient but also contains other synergistic mTOR signaling substances including L-Leucine, Beta-Hydroxy-Beta-Methylbutyrate (HMB), and Vitamin D3. Methods Eighteen healthy strength-trained males were randomly assigned to a group that either consumed MT (n  = 8, 22.0 +/− 2.5 years; 175.8 +/− 11.5 cm; 80.3 +/− 15.1 kg) or a placebo (PLA) (n  = 10, 25.6 +/− 4.2 years; 174.8 +/− 9.0 cm; 88.6 +/− 16.6 kg) as part of a double-blind, placebo controlled pre/post experimental design. All participants volunteered to complete the three day per week resistance training protocol for the eight week study duration. To determine the effects of MT, participants were tested on one repetition maximum (1RM) leg press strength (LP), 1RM bench press strength (BP), push-ups to failure (PU), vertical jump (VJ), pro-agility shuttle time (AG), peak power output (P), lean body mass (LBM), fat mass (FM), and thigh muscle mass (TMM). Subjects were placed and monitored on an isocaloric diet consisting of 25 protein, 50 carbohydrates, and 25 % fat by a registered dietitian. Separate two-way mixed factorial repeated measures ANOVA's (time [Pre, Post] x group [MT and PLA] were used to investigate strength, body composition, and other performance changes. Post-hoc tests were applied as appropriate. Analysis were performed via SPSS with significance at (p ≤ 0.05). Results There was a significant main effect (F(1, 16)  = 33.30, p  < 0.001) for LBM where MT significantly increased LBM when compared to the PLA group (p  < 0.001). Additionally, there was a significant main effect for LP (F(1, 16)  = 666.74, p  < 0.001) and BP (F(1, 16)  = 126.36, p  < 0.001) where both increased significantly more in MT than PLA group (p  < 0.001). No significant differences between MT and PLA were noted for FM, TMM, VJ, AG, P, or PU. Conclusion The results of this eight week trial suggest that the addition of MaxxTOR® to a 3-day per week resistance training program can positively impact LBM and strength beyond the results found with exercise alone.